A novel method to design tolerance of aero-engine casing by integrating 3-D assembly tolerance with performance instability. (June 2022) - Kang, Hehe; Li, Zhi-Min; Liu, Tao; Yuan, Wei; Wu, Yuping
Assembly quality of aero-engine casing plays a key role in the whole aero-engine, since it is directly related to the final function and dynamic performance. However, during the design phase, the tolerance analysis is usually conducted independently without any consideration of the effect on the dynamic characteristic. This paper aims to integrate manufacturing precision with dynamic performance instability together. First, the 3-D tolerance model of the aero-engine casing is constructed based on the Jacobian-Torsor theory. The target deviation from the tolerance model is defined as the input variable into the vibratory governing equation. Then, the effect of 3-D assembly deviation on the natural frequency is studied. The corresponding frequency distributions for different vibration modes are illustrated. Finally, the mapping relationship between assembly tolerance and fluctuation ratio of natural frequency is established through the 3-D fitted surface. Under the given constraint of performance stability, the optimized tolerance zone is obtained. This work provides a significant guidance for performance improvement and tolerance design in the aero-engine casing assembly.